Development of a prediction model for neonatal hypoglycemia risk factors: a retrospective study - Wu, Tian; Huang, Yi-Yan; Song, Wei; Redding, Sharon R.; Huang, Wei-Peng; Ouyang, Yan-Qiong (Frontiers in Endocrinology, 2023)
Background: It's challenging for healthcare workers to detect neonatal hypoglycemia due to its rapid progression and lack of aura symptoms. This may lead to brain function impairment for the newborn, placing a significant care burden on the family and creating an economic burden for society. Tools for early diagnosis of neonatal hypoglycemia are lacking. This study aimed to identify newborns at high risk of developing neonatal hypoglycemia early by developing a risk prediction model. Methods: Using a retrospective design, pairs (470) of women and their newborns in a tertiary hospital from December 2021 to September 2022 were included in this study. Socio-demographic data and clinical data of mothers and newborns were collected. Univariate and multivariate logistic regression were used to screen optimized factors. A neonatal hypoglycemia risk nomogram was constructed using R software, and the calibration curve and receiver operator characteristic curve (ROC) was utilized to evaluate model performance.Results: Factors integrated into the prediction risk nomogram were maternal age (odds ratio [OR] =1.10,